Reading strategies and reading comprehension for secondary school students. IE 7057 Sovereign Military Order of Malta. Lima. - Niño Solis , Liliana Farita (2025)
The purpose of the current study is to determine whether reading strategies are related to students' reading comprehension, I.E. N° 7057 Soberana Orden Militar de Malta. In this regard, a general hypothesis was nominated that there is a significant correlation between the use of reading strategies and students' reading comprehension at this institution. To obtain the necessary information on how data collection tools were selected, a statistically significant number of students were selected, as well as a study of reading strategy use and a reading comprehension test. This was completed based on the strong Spearman correlation (0.708) between reading strategies and reading. A P value of 0.000 gives significance. It is proposed that effective reading strategies have positive impacts on student reading. Finally, we appreciate those who have worked directly or indirectly with this study, and we hope the results obtained will be useful in initiating new research, enabling our students to improve.